THE PRACTICE OF FINANCIAL CONSULTANT SERVICE DILEMMA: THE LINK BETWEEN LIFE SUSTAINABILITY AND PRICING - Imtiyaz Farras Mufidah; Makaryanawati Makaryanawati (Yayasan Education and Social Center, 2021)
This study focuses on the practice of Financial Consulting Services regarding survival with pricing. The difference between this research and previous research is that it is still not optimal in determining the price of consulting services. It is still rare to conduct research related to survival in Financial Consulting Services. This qualitative research focuses on case studies with an interpretive paradigm. In a survival growth strategy, X's financial consulting services use word of mouth (WOM) communication strategy to expand market reach. X's own financial consulting services have a dilemma when faced with small clients who only pay a low fee for consulting services. In the end, the consulting procedures carried out must be adequate to maintain the quality of consulting services, where Financial Consulting Services X has pricing policy guidelines and cuts the level of consulting leveling. Rules that are more accomodating to small clients in the area are needed regarding compensation for Financial Consulting Services